Students' Voices: Navigating Written Corrective Feedback in English Language Learning - Tohamba, Citra Prasiska Puspita (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2026)
Written Corrective Feedback (WCF) remains a widely practiced instructional strategy in English as a Foreign Language (EFL) classrooms, particularly for improving students’ writing accuracy, yet debates continue regarding its pedagogical value and the ways learners actually respond to it. While existing studies have examined the technical aspects of WCF, fewer have investigated how students perceive its usefulness and how their emotional reactions shape engagement with feedback. This study seeks to explore these dimensions by analyzing students’ preferences for different feedback types, their evaluations of WCF’s effectiveness, and the affective responses that accompany the process. Adopting a qualitative design, data were collected through surveys and semi-structured interviews with EFL learners from diverse academic backgrounds. The results suggest that although students generally recognize WCF as an essential tool for language development, their preferences vary: some favor direct feedback for its clarity, others prefer indirect or metalinguistic feedback for encouraging self-correction. Emotional responses were equally diverse, ranging from motivation, reassurance, and appreciation to frustration, anxiety, and even discouragement when feedback was perceived as overly critical. These emotional factors proved influential in determining the extent to which learners engaged with and acted upon the corrections provided. The study concludes that effective feedback practices require a balance between corrective and supportive elements, enabling learners to benefit cognitively while also maintaining confidence and resilience in the face of error correction. The findings hold significant implications for language teachers, emphasizing the importance of adopting feedback strategies that attend simultaneously to students’ linguistic needs and their affective well-being in order to cultivate sustainable writing development.